2015
DOI: 10.1097/jcp.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Lithium-Associated Hyperparathyroidism in a Large Swedish Population Attending Psychiatric Outpatient Units

Abstract: The prevalence of LHPT is high and often goes undetected. Vitamin D insufficiency is common as is polypharmacy. Surgery, for unclear reasons, has not been performed extensively, possibly because of limited knowledge of the underlying pathophysiology or surgery's significance. We present standard recommendations on patient management and suggest continual, specific follow-up including the monitoring of calcium, PTH, and vitamin D at least annually. Surgery should be considered with intention to improve psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…LAH is characterised by mildly elevated calcium levels (Fig. 2 ), which occur chronically or intermittently [ 13 , 14 ]. Despite numerous articles highlighting the credible association between lithium and the development of hypercalcemia, the monitoring of parathyroid function has only recently been included in the revised recommendations of NICE [ 15 ] and the International Society for Bipolar Disorder [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAH is characterised by mildly elevated calcium levels (Fig. 2 ), which occur chronically or intermittently [ 13 , 14 ]. Despite numerous articles highlighting the credible association between lithium and the development of hypercalcemia, the monitoring of parathyroid function has only recently been included in the revised recommendations of NICE [ 15 ] and the International Society for Bipolar Disorder [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia in lithium-treated patients with BPD was not correlated with kidney function, and even moderate chronic kidney insufficiency proved to be statistically insignificant (Table 3 ). The significance of hypercalcemia for the lithium-treated individual is unclear [ 14 ]. The GAF instrument did indicate that individuals with lithium treatment scored lower on this assessment of psychosocial functioning (Tables 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since its first description by Garfinkel et al in 1973 another possible cause for pHPT has been revealed: HPT associated with lithium medication [11]. Since then, about 300 cases of lithium-associated HPT (LIHPT) were described in cohort studies and case presentations [12].…”
Section: Contextmentioning
confidence: 99%
“…However, despite beneficial action, the therapy may carry side-effects, affecting both life conditions and compliance of patients in a considerable way. Lithium's side-effects include hypercalcaemia, gastrointestinal, dermatological, cardiovascular, renal, as well as thyroid and parathyroid disorders [2,7,8,9,10,11,12]. Research has revealed its harmful influence on the functions of key organs, including liver and kidney [2,10,13,14] with the latter being particularly vulnerable [3,15,16].…”
Section: Introductionmentioning
confidence: 99%